Penerapan Rantai Markov Dalam Memprediksi Probabilitas Return INDF - Dian Firmayasari S; Nurhalisa; Izhar Taufiq Hidayat (Mathematics Study Program, Faculty of Mathematics and Natural Science, Udayana University Gedung UKM, Ruang UKM 8 Lt 1, Kampus Bukit Jimbaran, Badung-Bali., 2025)
Investing in stocks in the capital market not only provides profits but also involves various potential risks that may arise in stock investments. Investments are made to generate returns, so it is necessary to calculate the returns. In predicting stock prices. One method that can be used is the Markov chain method. Stock price movements can be categorized as a Markov chain, where patterns may repeat, but the exact timing of their occurrence cannot be precisely determined. The objective of this study is to predict the return on INDF stock from April 2025 to July 2025 using the Markov chain method. The research results indicate that, based on the obtained results, it can be concluded that by the 7th day, the INDF stock return has reached a steady state or stable condition. This means that the prediction of the INDF stock return no longer depends on the initial condition (first day) or the probability of the return does not change on subsequent days. In other words, the probability of the stock return experiencing a loss, remaining the same, or achieving a gain is 34% for the next day.